Wandering in circles : Venichka's journey of redemption in Moskva-Petushki - Martiniuk, Jill, 1981- (Academic Studies Press, 2022)
"Wandering in Circles: Venichka's Journey of Redemption in "Moskva-Petushki" examines the definition of redemption in Venedikt Erofeev's Moskva-Petushki. By placing Erofeev's poema in conversation with other travel narratives from Russia and the West, the book explores the meaning of redemption across societies and cultures, and how Erofeev creates a commentary on the possibility of redemption in a broken political and social system. Through this comparative approach to Moskva-Petushki, this work offers a new reading of the text as a journey of failed social and personal redemption"--